PERINEAL MASSAGE: PREVENTING PERINEAL EPISIOTOMY AND PERINEAL LACERATION DURING CHILDBIRTH - Shinta Wurdiana Rhomadona; Minarni Hardianti (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Backgrounds: Approximately 4-5% of maternal deaths in Indonesia is caused by trauma in the birth canal, of which perineal laceration and episiotomy are the most common occurrence. Generally, as much as 80- 90% of episiotomies are performed on first-time mothers (primipara). Episiotomy can be prevented by perineal massage from 34 weeks gestation. Aims: To reveal a picture of episiotomy implementation in primiparous mothers who received perineal massage at BPM (Independent Clinic of Midwifery) Istiqomah in Sidotopo, Surabaya . Methods: This research used descriptive method. The population were primiparous mothers who received perineal massage. The sample of 20 mothers were chosen by consecutive sampling technique. This research used perineal massage as the independent variable and episiotomy and perineal laceration as the dependent variables, and was measured using the observation sheet during childbirth. The data was then processed by using a frequency distribution table. Results: The results showed that out of 20 respondents who received perineal massage, only four had done an episiotomy during childbirth. Each of these four women had complicated condition - three of whom had fetal distress and one had an exhausted childbirth process. Conclusion: The main benefit of performing perineal massage during episiotomy procedure is to relax the muscles surrounding the perineum and make them more elastic.